MINERALIZED BOVINE BONE GRAFTING IN THE MAXILLARY SINUS USING THE LATERAL WINDOW TECHNIQUE: A CLINICAL CASE REPORT (REMUNOM, 2026)
This study aimed to report a clinical case where maxillary sinus elevation and filling with bovine inorganic bone matrix graft were performed using the lateral window technique. A male patient attended the oral rehabilitation clinic of the Implantology postgraduate program at the Institute of Science and Technology - São José dos Campos Campus (UNESP) with a complaint of missing teeth. Clinical and radiographic examination revealed maxillary sinus pneumatization and insufficient bone thickness in the posterior maxilla for implant installation. The proposed treatment involved maxillary sinus elevation and filling with biomaterial, and after 1 year, two implants were placed in the 25 and 26 regions with implant stability achieved above 35 Ncm.